1998
DOI: 10.1152/ajpheart.1998.275.2.h641
|View full text |Cite
|
Sign up to set email alerts
|

α1-Adrenergic activation of myocardial Na-K-2Cl cotransport involving mitogen-activated protein kinase

Abstract: The translocation mechanisms involved in the α1-adrenoceptor-stimulated efflux of the potassium analog86Rb+were studied in isolated rat hearts. Phenylephrine (in the presence of a β-blocker) increased the efflux of86Rb+and42K+, and the Na-K-2Cl (or K-Cl) cotransport inhibitor bumetanide reduced the response by 42 ± 11%. Furosemide inhibited the response with a lower potency than that of bumetanide. The bumetanide-insensitive efflux was largely sensitive to the K+ channel inhibitor 4-aminopyridine. Inhibitors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…In addition, it has been shown that stimulation of NKCC activity is MAPK dependent in striated muscle (2,31). The present study demonstrates that ␤-AR stimulation can activate fiber phenotype-specific signaling cascades that involve both G s -and G i -coupled processes.…”
supporting
confidence: 59%
“…In addition, it has been shown that stimulation of NKCC activity is MAPK dependent in striated muscle (2,31). The present study demonstrates that ␤-AR stimulation can activate fiber phenotype-specific signaling cascades that involve both G s -and G i -coupled processes.…”
supporting
confidence: 59%
“…This suggests that ERK1/2 can regulate other ion transporters independently of NHE-1. The possible targets for ERK1/2 that could contribute to the cytosolic Na ϩ and Ca 2ϩ load include the Na ϩ -K ϩ -2Cl Ϫ cotransporter, which is activated by ␣ 1 -adrenergic agonist in an ERK1/2-dependent mechanism in cardiac myocytes (2), or the Na ϩ -HCO 3 Ϫ cotransporter, which is coupled to muscarinic receptor activation by ERK1/2 in renal epithelial cells (30). We cannot rule out the possibility that ERK1/2 can directly modulate NCX or Na ϩ /K ϩ pump activity that could also contribute to alterations in Ca 2ϩ or Na ϩ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Hearts from deeply ether-anesthetized adult male Wistar rats (200-250 g) were excised and placed into ice-cold saline. The hearts were retrogradely aorta perfused as described in detail previously (3). The hearts were spontaneously beating and perfused in a nonrecirculating system at 31°C and at a constant flow of 10 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a myocardial NKCC was suggested early by the findings of loop diuretic-sensitive ion transport (mainly K ϩ or the potassium analog 86 Rb ϩ ) in heart preparations from different species (8,12,14,21). A more extensive characterization of myocardial Na-K-2Cl cotransport is lacking, but we have previously reported that both ␣ 1 -adrenoceptor (AR) and angiotensin II receptor stimulation activated bumetanide-sensitive 86 Rb ϩ efflux in perfused rat hearts (2,3). We found that ␣ 1 -AR-induced activation of bumetanide-sensitive 86 Rb ϩ efflux was blocked by a specific inhibitor of MAPK kinase (MAPKK or MEK1) activation, suggesting that the bumetanide-sensitive 86 Rb ϩ efflux is regulated by an extracellular signal-regulated protein kinase (ERK)-dependent pathway (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation